PENGARUH INHALASI MINYAK KAYU PUTIH (Melaleuca leucadendron) TERHADAP GAMBARAN HISTOLOGI LAMBUNG MENCIT JANTAN (Mus musculus) YANG DIINDUKSI STRES AKUT - Brigita Elsa Kabrahanubun; Halidah Rahawarin; Yuniasih M.J Taihuttu; Juliet Sinanu; Indrawati Kushadiani (Fakultas Kedokteran Universitas Pattimura, 2022)
Damage on gastric mucosa is caused by an imbalance of defensive factors and aggressive factors. This can be due to various factors, one of which is stress. Cajuput oil as aromatherapy is proven to prevent stress because it contains 1,8 cineole, α-terpineol, and 4-terpineol which have a sedative-hypnotic effect. This study aims to determine the effect of inhalation of cajuput oil on the gastric histology of mice. This research is a true experimental with a post test only control group design. The research subjects were 16 adult male mice taken by simple random sampling and divided into normal group (KN), negative control group (K-), positive control group (K+), and cajuput oil inhalation group (P). Groups K+, K-, and P were given stress treatment with the Tail Suspension Test (TST) method for six minutes for 14 day. Surgery was perfomed on the 15th day and histology preparations were made. The average score of gastric mucosal damage in cajuput oil group was lower when compared to the stress group although the results of the Tukey test showed no significant results between these two group. It can be concluded that cajuput oil with an inhalation dose 0.5 mL has anti-stress effect that prevent gastric mucosal damage in mice which acute stress induced.